Non-Fatal Strangulation/Choking During Sex and Its Associations with Mental Health: Findings from an Undergraduate Probability Survey. Issue 3 (1st April 2022) - Herbenick, Debby; Fu, Tsung-chieh; Kawata, Keisuke; Eastman-Mueller, Heather; Guerra-Reyes, Lucia; Rosenberg, Molly; Valdivia, Dubravka Svetina
Abstract: Choking/strangulation during sex is prevalent among young adults in the United States. We examined associations between having ever been choked and participants' current mental health symptoms (e.g., feeling depressed, anxious, sad, lonely) in the prior 30 days and in the prior year. Participants were 4352 randomly sampled undergraduates who completed a confidential online survey and reported lifetime partnered sexual activity. 33.6% of women and 6.0% of men reported having been choked more than five times. After adjusting for demographic characteristics, having been choked remained significantly associated with all four mental health outcomes, except for overwhelming anxiety among men.